Outcomes of laparoscopic sacrocolpopexy using self-cut mesh on pelvic organ prolapse - Alfa Putri Meutia; Suskhan Djusad; Tyas Priyatini; Kevin Yonathan; Tokumasa Hayashi; Jimmy Nomura (Urology Annals)
Objectives: The objective of the study was to investigate the long-term outcome and complication rate of laparoscopic sacrocolpopexy (LSC) using self-cut mesh as pelvic organ prolapse treatment. Methods: A retrospective cohort study on patients undergoing LSC was done at Kameda Medical Center from January 2013 to January 2018. Data for this study were taken from all women with pelvic organ prolapse who had undergone LSC using self-cut polypropylene mesh. Patients with a previous history of hysterectomy were excluded from the study. An evaluation was done preoperatively, on 6-month and 1-year postoperative follow-up period using Pelvic Organ Prolapse Quantification (POP-Q) and The International Consultation on Incontinence Questionnaire-short form (ICIQ-SF) questionnaire. Results: There were 702 subjects who met the inclusion and exclusion criteria. The clinical characteristics of the subjects were recorded. The scores during admission, 6 months and 1 year postoperative are: POP Q scores: 6.50 ± 5.69 vs. 5.11 ± 4.85 vs. 4.78 ± 4.31, P = 0.049 and ICIQ SF scores: 2.92 ± 0.62 vs. 1.10 ± 0.36 vs. 1.13 ± 0.41, P < 0.001). A total of 17 (2.4%) perioperative and postoperative complications were observed on subjects. Conclusion: LSC using self-cut mesh could produce satisfactory results in pelvic organ prolapse patients on 6-month and 1-year follow-up period with minimal perioperative complications.